Modelagem e análise do protocolo de roteamento Leach - Silva, Luana Barreto da (2014)
The Wireless Sensor Networks (WSN) are self-organized systems made by nodes that communicate each other changing information and giving support in many fields. But, these networks have some limitations because the lack of resources, especially power supply. This limitation it is because, in general, the sensors have limited power supply on their battery and there is no possibility of reload this energy. But to garantee its purpose the WSN should have effective communication. The choice of a wrong routing protocol on a WSN can lead to a bad use of network resources, which leads to a less time of live and/or reducing the quality of data transmitted. Among the existing routing protocols in the literature, highlight the Leach. In this work, we performed the modeling and analysis of Leach routing protocol using Petri Nets. Simulations were performed with the NS for its validation. To analyze the performance metrics are studied as: energy savings of each node, lifetime and throughput. From the analysis of the results was possible to propose improvements to the protocol, resulting in the implementation of a new routing protocol for WSN, Leach Lua. The results showed that the Leach Lua is able to provide improvements in the metrics studied when applied in scenarios that include the use of WSNs for monitoring of fires, oil fields and vital signs of medical patients.